Enriching of society’s understanding of command-oriented leadership through an interactive virtual discussion - Mirad Fahri; Elva Stiawan; Dita Ariyanti; Rahmat Basuki; Yusuf Bramastya Apriliyanto; Anggi Khairina Hanum Hasibuan; Tedi Kurniadi; M. Sulthon Nurharmansyah Putra; Dewi Septaningsih; Sekar Ilma Tiarani; Ersha Mayori; Regita Andriani Wiana; Amalia Yunita; Naufan Nurrosyid; Agus Eko Prasojo; Riyanti Putri (Universitas Muhammadiyah Malang, 2024)
In the post-pandemic era, many interactive activities have been flexibly generated through virtual conditions. Accordingly, some problems could appear in terms of leadership, such as difficulties in maintaining the audience’s attention during the event. Thus, the utilization of a command-based leadership style that could straightforwardly maintain audience focus ought to be considered to be adopted. However, both the command-based leadership style and its prospective aspects have not been widely understood by society. This community service aims to deliver a proper understanding of the command-based leadership style through interactive virtual discussion between experts in teaching activities of defense-based science and society consisting of Indonesian teachers, high school students as well as academics. Statistical results of pre-test and post-test scores showed enhancement of the participants’ understanding of command-based leadership. Hopefully, some relevant aspects of their new perspective of command-based leadership can be properly adopted and effectively implemented to answer current challenges, such as in terms of managing people in virtual conditions.